Alarms and Diversions - Thurber, James frey50 (Harper & Brothers Publishers New York, 1957)
A book for people who like to laugh and know how to think, selected from Thurber's work over 30 years - one third of the text never before in book form.
1. The ladies of Orlon ; The first time I saw Paris ; The psychosemanticist will see you now, Mr. Thurber ; It's your Mother ; Two o'clock at the Metrople ; Get thee to a monastery ; A holiday ramble ; "There's something out there!" ; The moribundant life, or, Grow old along with whom? ; Merry Christmas -- 2. A gallery of drawings -- 3. File and forget ; A sort of genius ; The waters of the moon ; Exhibit X -- 4. A new natural history -- 5. A final note on Chanda Bell ; There's a time for flags ; Am not I your Rosalind? ; The French far West -- 6. The masculine approach -- 7. A friend to Alexander ; The figgerin' of Aunt Wilma ; Mr. Punch ; The white rabbit caper ; My own ten rules for a happy marriage -- 8. The race of life -- 9. The interview ; Daguerreotype of a lady ; A call on Mrs. Forrester ; There's no place like home ; The lady on the bookcase -- 10. A miscellany -- 11. Do you want to make something out of it? ; The whip-poor-will ; The ordeal of Mr. Matthews ; Lavender with a difference -- 12. The last flower.
Keywords: Humorous stories -- American